Use of tobacco, nicotine and cannabis products among students in Switzerland - Affolter, Jana; Rohland, Eveline; Philippe, Marc; Tal, Kali; Auer, Reto; Jakob, Julian (Frontiers in Public Health, 2023)
Introduction: Most of the people who smoke began in their teens. Teens may be equally attracted to new tobacco, nicotine, and cannabis products. We described use prevalence among students, including daily use, of tobacco, nicotine, and cannabis products, in Switzerland. Methods: We invited students at the upper secondary school level in two Swiss cantons to participate in an online survey between October 2021 and February 2022. The survey asked participants for demographic information and how often they used tobacco products (cigarettes in commercial packages, self-rolled cigarettes, hookahs, pipes, cigars and cigarillos, tobacco heating systems, snus, snuff), non-tobacco nicotine products (nicotine pouches, e-cigarettes with and without nicotine) and cannabis products (smoking with and without tobacco, cannabis vaping). Answers were scored on a Likert scale (no use in past month, less than weekly, weekly but not daily, daily use, prefer not to say). We tabulated the responses and reported descriptive statistics. Results: Of the 32,614 students who were invited to participate, 9,515 students completed the survey (29.2%); 49.5% identified as female and 48.4% as male. 9.5% were under 16, 47% 16-17, 27.5% 18-19, and 16% over 19. Reported daily use was most frequent for tobacco cigarettes in commercial packages (14.2%), snus (4.1%) and cannabis smoking with tobacco (3.6%). Most participants (54.8%) reported they had used at least one product at least one time within the last month. Conclusion: Students using a product are most likely to smoke cigarettes, but many regularly use new tobacco, nicotine and cannabis products, though use frequency varies.